Effects of inorganic nitrate and nitrite consumption on cognitive function and cerebral blood flow: A systematic review and meta-analysis of randomized clinical trials. Issue 15 (22nd August 2019) - Clifford, Tom; Babateen, Abrar; Shannon, Oliver M.; Capper, Tess; Ashor, Ammar; Stephan, Blossom; Robinson, Louise; O'Hara, John P.; Mathers, John C.; Stevenson, Emma; Siervo, Mario
ABSTRACT: We conducted a systematic review and meta-analysis of randomized clinical trials examining the effect of inorganic nitrate or nitrite supplementation on cognitive function (CF) and cerebral blood flow (CBF). Two databases (PubMed, Embase) were searched for articles from inception until May 2017. Inclusion criteria were: randomized clinical trials; participants >18 years old; trials comparing a nitrate/nitrite intervention with a control. Thirteen and nine trials were included in the meta-analysis to assess CF and CBF, respectively. Random-effects models were used and the effect size described as standardized mean differences (SMDs). A total of 297 participants (median of 23 per trial) were included for CF; 163 participants (median of 16 per trial) were included for CBF. Nitrate/nitrite supplementation did not influence CF (SMD +0.06, 95% CI: -0.06, 0.18, P = 0.32) or CBF under resting (SMD +0.14, 95% CI: -0.13, 0.41, P = 0.31), or stimulated conditions (SMD + 0.23, 95% CI: -0.11, 0.56, P = 0.19). The meta-regression showed an inverse association between duration of the intervention and CBF (P = 0.02) but no influence of age, BMI or dose ( P < 0.05). Nitrate and nitrite supplementation did not modify CBF or CF. Further trials employing larger samples sizes and interventions with longer duration are warranted.